Groundwater pumping simulation using hydrology apparatus - Nuradibah, Zainaludin (2015)
Groundwater is water located beneath the ground surface and underground water movement in soil and rocks. There are many method of obtaining hydraulic information from aquifers, but perhaps the most common and best is the pumping test or aquifer test. Without an estimate of the hydraulic properties of an aquifer, calculation of groundwater movement cannot be performed with any level of confidence. In other word, pumping test is the best method to obtain the hydraulic information. Objective of this study is to relate the relationship of the groundwater flow due to the pumping activities using 2 different conditions and determine the value of hydraulic conductivity (k) due to uniform size of sand. In more advance, the objective of this study to prove the Darcy’s Law equation is relevant to applied in the study of groundwater flow. This study was carried out by using hydrology apparatus in the laboratory UMP with single and double mode pumping condition. The measurement of piezometer head showed the illustration of water table drawdown in the ground when using same size of sand which is 0.75 mm in the catchment area. There are 12 cases condition with 3 different initial groundwater levels which are 65 mm, 100 mm and 135 mm. This study was carried out in confined and unconfined aquifer Even though the flow rate, Q was set different value, hydraulic conductivity, k show that it still in the range of 0.01-10 mm. Data from the laboratory was compared with the value that stimulated from Darcy’s Law equation. The value of differences were not much different and its can be proved that the equation is valid to apply in the hydrology field especially in groundwater pumping study. The result of this study highlighted the effect of pumping activities on water table: higher rate of pumping could cause the higher drawdown of water table especially at the well point. Then, if the pumping rate is too slow, a small cone of depression will result and the drawdown in observation well may be detected. Conversely, if pumping rate are too high, then the test will not run very long because the pumping level will reach the pump.